1982
DOI: 10.1159/000459111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sex Hormones on the Activities of Hepatic Alcohol-Metabolizing Enzymes in Male Rats

Abstract: In mature male rats both estradiol administration as well as castration had a striking suppressive effect on the hepatic activity of the microsomal ethanol-oxidizing system, whereas alcohol dehydrogenase activity was increased under these experimental conditions. The castration effects on the activities of the alcohol-metabolizing enzymes could be completely prevented by the administration of testosterone. Therefore, these results indicate the sex-dependent nature of the hepatic microsomal ethanol-oxidizing sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Studies have shown that hepatic ADH-specific activity is higher in female rats compared with males (4,9,51,52), but the mechanism(s) is unclear. Androgens downregulated ADH-specific activity in some studies (37,40,43), but not others (9,10), whereas estrogens increased hepatic ADH-specific activity in male rats but not females (41,57,58). Furthermore, it is unclear whether sex steroid hormones alter ADH activity directly in the liver or rather through modulation of the GH secretory pattern (9).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that hepatic ADH-specific activity is higher in female rats compared with males (4,9,51,52), but the mechanism(s) is unclear. Androgens downregulated ADH-specific activity in some studies (37,40,43), but not others (9,10), whereas estrogens increased hepatic ADH-specific activity in male rats but not females (41,57,58). Furthermore, it is unclear whether sex steroid hormones alter ADH activity directly in the liver or rather through modulation of the GH secretory pattern (9).…”
Section: Discussionmentioning
confidence: 99%
“…However, the relations between the activi ties of ADH and of ethanol metabolism in mice liver is unknown. Teschke et al reported that sex hormones such as testosterone and estradiol affect the hepatic MEOS in rats (20), and Lieber and Decarli reported that the activity of the MEOS of male rats was higher than of female rats (21). Gender-related differences were also recognized in the hepatic and renal microsomal CYP2E1-dependent metabolism of steroids (22) and xenobiotics (23) in rats and mice.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens suppress MEOS, whereas testosterone restores enzyme activity in castrated animals. 5 There are important differences in alcohol-metabolizing capacity of ADH and MEOS. The microsomal ethanol-oxidizing system is an inducible enzyme, and its activity increases at higher levels of alcohol consumption, while ADH levels remain constant with alcohol use.…”
Section: Methods and Resultsmentioning
confidence: 99%